? asked in Science & MathematicsEngineering · 9 years ago

solve for the ff.equation?

2x-5/4x-1=3x-4/6x+9?

3 Answers

Relevance
  • 9 years ago
    Favorite Answer

    2x-5/4x-1=3x-4/6x+9? , it is confusing, if it is 2x - 5x/4 -1 = 3x - 4x/6 +9

    then shifting -1 to RHS and 3x - 4x/6 to LHS, we get

    2x - 5x/4 - 3x + 4x/6 = 9+1

    Multiply both side by 12

    24x - 15x - 36x + 8x = 10x12 = 120

    or 32x - 51x = -19x = 120, or x= -120/ 19

  • 9 years ago

    21

    Source(s): yes
  • 9 years ago

    2x-5/4x-3x-4/6x = 9+1

    8/4x-5/4x-1=9/3x-2/3x+9

    3/4x-1=7/3x+9

    3/4x-7/3x=9+1

    9/12x-28/12x=10

    -19/12x=10

    x=-120/19

Still have questions? Get your answers by asking now.